Determinants of hedging: a review of theoretical studies - Omar, Abdullah; Taufil Mohd, Kamarun Nisham; Ahmad, Norzalina (2017)
Hedging instruments are deemed as value enhancing tool for both financial and non financial firms. The aim of this study is to highlight those theoretical studies which are written in context of hedging determinants. Theoretical studies argued that in a world with no taxes, no transaction costs, and with fixed investment policies, hedging with derivatives is irrelevant to firm value. However, some studies suggests that derivative instruments can increase firm value when the premises of a perfect market have been relaxed, since they can eliminate corporate tax liabilities, financial distress costs, dependence on costly external financing, and agency costs.